Knowledge creation capabilities for human capacity development in SMEs construction company in Sabah - Elmi Alif Azmi,; Nurul Elma Kordi,; Che Khairil Izam Che Ibrahim,; Anitha Ravishankar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In SME construction company, knowledge creation is important for organizational competitiveness and survival. Ability to create new knowledge is one of the vital assets for an organization to keep being competitive. In previous research, studies have been widely conducted in knowledge management and focus on large organizations in high technology sectors. This paper seeks to explore the current implementation of knowledge creation capabilities in SMEs construction company in Sabah. The attributes and barriers of knowledge creation in SMEs organization that can affect the organizational performance were investigated. This study also proposed the mitigation measures to the barriers of knowledge creation in the SMEs organization. Critical literature review and quantitative method were used to achieve the objectives of this study. An online questionnaire will be distributed to identify the attributes and barriers of knowledge creation and its mitigation measures in SME construction companies in Sabah. The data obtained from the questionnaire were analysed using Statistic Package for the Social Sciences (SPSS) by descriptive analysis. The attributes of knowledge creation in SMEs organization have been identified: learning/education, IT adjustment, and collaboration, while the critical barriers: poor training, practice, poor T-shaped skills, and ineffective knowledge & information communication. The most critical mitigation measures that should be taken to remove the barriers: develop an effective knowledge management system, provide education, training, and development practice, and build ethical organization culture. The paper also provide recommendation for future research.